The Impact of Content Marketing and Influencer Credibility on Purchase Intention among Generation Z Consumers in Indonesia - Vania Amanda Fersa; Paradita Kusumarina; Omiya Nurul Shakina; Kartika Putri Utami Ilham; Yudhinanto (International Journal of Business and Quality Research, 2026)
This study aims to examine the effect of content marketing and influencer credibility on purchase intention among Generation Z consumers in Indonesia. This research employed a quantitative approach with an explanatory research design. Data were collected through an online survey using a five-point Likert scale questionnaire. The respondents consisted of 104 Generation Z individuals aged 17–28 years who actively use social media and are exposed to digital marketing content in Indonesia. Data analysis was conducted using multiple linear regression. The findings indicate that content marketing and influencer credibility simultaneously have a significant effect on purchase intention. Partially, content marketing has a positive and significant influence on purchase intention, while influencer credibility does not show a significant effect. The coefficient of determination reveals that both independent variables explain 59.7% of the variance in purchase intention. The study concludes that content marketing plays a more dominant role than influencer credibility in influencing the purchase intention of Generation Z consumers. Effective and relevant content is a key factor in stimulating buying interest among this generation. This study is limited by the relatively small sample size and the use of self-reported data, which may not fully represent all Generation Z consumers in Indonesia. This research contributes to the field of digital marketing and consumer behaviour by providing empirical evidence on the effectiveness of content marketing for Generation Z.